Diagnóstico morfológico e molecular das principais enfermidades que acometem cachorro-do-mato (Cerdocyon thous) no Espírito Santo. - Uzai, Gabriel José Silva (2019)
The crab-eating fox (Cerdocyon thous) is a species of wild canid that occurs in much of South America. Although they are considered omnivores, they have general habits and eventually feed on carcasses of domestic animals, as well as processed food and food waste from areas where there is human occupation and domestic animals. This relationship of proximity represents a risk for an occurrence of diseases in this species. Thus, the present study proposed an investigation of diseases in Cerdocyon thous of free life victims of trampling on the highways of Espírito Santo State, Brazil. For this, two tests were developed: detection of Brucella sp., Babesia sp., Rangelia sp. and Hepatozoon sp. in spleen samples of C. thous and the evaluation morphological and identification of parasites in liver and lung samples from C. thous. Nineteen animals were necropsied in the Animal Pathology Laboratory of the Federal University of Espírito Santo and were evaluated by PCR and histopathology. A kind of polymerase chain reaction for the infectious agents Brucella sp., Babesia sp., Rangelia sp. and Hepatozoon sp. did not reveal target object DNA magnification in any sample. In view of this, it is concluded that were not detected the infectious agents Brucella sp., Babesia sp., Rangelia sp. and Hepatozoon sp. in crab-eating fox of free life from Espírito Santo, however, in the liver and lung were observed lesions associated with parasitism by Platinosomum sp. and Angiostrongylus sp., respectively. In this way, it is important that more studies are done to clarify the role of the crab-eating fox in the transmission of diseases and / or parasites, since this animal can act as a sentinel, the same reservoir of many diseases.